Was that capitalism? A future-oriented big data analysis of the English language area in the 19th and 20th century. (April 2018) - Roth, Steffen; Valentinov, Vladislav; Augustinaitis, Arūnas; Mkrtichyan, Artur; Kaivo-oja, Jari
Highlights: Foresight and futures studies depend on the adequacy of our knowledge of the present and the past. Big data evidence suggests that the English language area was not capitalist between 1800 and 2000. Popular social macro trend statements ought to be scrutinised to reduce the risk that inadequate trend assumptions are projected into the future. Abstract: As foresight and futures studies depend on the pertinence of our knowledge of the present and the past, this article tests whether the English language area may be adequately described as secularised and capitalist between 1800 and 2000. We are using the Google Ngram Viewer to chart and interpret time series plots of combined frequencies of pertinent keywords in the largest Internet book corpus, the Google Books corpus. The results suggest that the English language area is a secularised, politicised, scientificised, and ultimately also mediatised language area which has never been dominated by the economy. We conclude that the sample period may not be characterised as capitalist if we associate capitalism with any form of over-average importance or even dominance of the economy and suggest that popular social macro trend statements be regularly turned from implicit assumptions into explicit research questions so as to reduce the risk that inadequate trend assumptions are projected into the future.